The Influence of Social Media Advertising Content on the Number of Leads Through Direct Messages for Excel Products at Edspert - Dewi Ramadani; Budi Astuti (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of social media advertising content on the number of Direct Message (DM) leads for Edspert's Excel training product, as well as coordination between the Marketing and Sales teams in approving incoming leads. The research was conducted during an internship program at PT Widya Kreasi Bangsa, an EdTech company specializing in professional competency development through the Edspert.id platform. The method used was a qualitative case study approach. Data collection was conducted through in-depth semi-structured interviews, observation, and documentation. The interviewees included the Performance and Growth Marketing (PGM) team, Edspert's Business Development & Sales team, and Excel training participants as supporting sources. Data validity was tested using source triangulation. The results revealed two main findings. First, the social media advertising content used by Edspert was not fully optimal in encouraging audiences to engage with Direct Messages. This was due to the lack of differentiation in content types tailored to the characteristics of each platform, a content strategy that was not fully relevant to the target audience segment, and limited human resources within the PGM team. Second, there are still gaps in coordination between the Marketing and Sales teams, particularly in the delivery of campaign information, which is not always fully conveyed to the Sales team, leading to miscommunication that impacts lead follow-up. Nevertheless, the overall lead handling process is quite structured, and the quality of incoming leads is considered quite good. This study recommends that Edspert differentiate content based on platform and audience segment, strengthen cross-divisional coordination, and ensure information alignment between the Marketing and Sales teams to improve the effectiveness of digital campaigns and the conversion of leads into training participants.